Reimagining Digital Governance: E-Government Transformation in Accelerating Bureaucratic Reform in Mataram City - M. Ulfatul Akbar Jafar; Asfarony Hendra Nazwin; Cahyadi Kurniawan; Afriadin Afriadin; Fairus Sumaya (Indonesian Journal Publisher, 2026)
This study aims to analyze the transformation of e-government in accelerating bureaucratic reform through the implementation of digital governance in Mataram City. This research is motivated by the demand for improving the quality of effective, transparent, accountable, and technology-based public services in the era of digital transformation. The implementation of e-government is seen as a strategic instrument in realizing modern governance that is able to increase the efficiency of public administration and strengthen public participation. However, the implementation of digital government in the regions still faces various challenges, such as limited system integration, human resource capacity, technological infrastructure, and community digital literacy. This study uses a qualitative approach with a descriptive research type. Data collection techniques are carried out through observation, documentation, and literature studies related to the implementation of the Electronic-Based Government System (SPBE) in Mataram City. Data analysis uses the interactive model of Miles, Huberman, and Saldaña which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of e-government in Mataram City has contributed significantly to the acceleration of bureaucratic reform by increasing the efficiency of public services, information transparency, bureaucratic accountability, and the effectiveness of government administration. Digital transformation is realized through online-based population administration services, a digital licensing system, a public complaints application, and the integration of government information systems. This study concludes that strengthening digital governance through digital system integration, human resource capacity development, improving information technology infrastructure, and strengthening literacy and public participation are crucial factors in realizing sustainable digital bureaucratic reform in Mataram City